Leopardi and heroicomic poema. A matter to be reconsidered (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
The essay investigates Leopardi’s relationship with the heroicomic tradition. Starting from the youthful Arte poetica travestita ed esposta in ottava rima, through the three translations of Homeric Batracomiomachia, and up to the late Paralipomeni, the question of the presence of the heroicomic in Leopardi’s work is reconsidered, identifying new perspectives of investigation in relation to ancient and modern authors.
Keywords: Giacomo Leopardi; Batracomiomachia; Paralipomeni della Batracomiomachia; heroicomic